Mapping lead concentrations in urban topsoil using proximal and remote sensing data and hybrid statistical approaches. (1st March 2021) - Shi, Tiezhu; Yang, Chao; Liu, Huizeng; Wu, Chao; Wang, Zhihua; Li, He; Zhang, Huifang; Guo, Long; Wu, Guofeng; Su, Fenzhen
Abstract: Due to rapid urbanization in China, lead (Pb) continues to accumulate in urban topsoil, resulting in soil degradation and increased public exposure. Mapping Pb concentrations in urban topsoil is therefore vital for the evaluation and control of this exposure risk. This study developed spatial models to map Pb concentrations in urban topsoil using proximal and remote sensing data. Proximal sensing reflectance spectra (350–2500 nm) of soils were pre-processed and used to calculate the principal components as landscape factors to represent the soil properties. Other landscape factors, including vegetation and land-use factors, were extracted from time-sequential Landsat images. Two hybrid statistical approaches, regression kriging (RK) and geographically weighted regression (GWR), were adopted to establish prediction models using the landscape factors. The results indicated that the use of landscape factors derived from combined remote and proximal sensing data improved the prediction of Pb concentrations compared with useing these data individually. GWR obtained better results than RK for predicting soil Pb concentration. Thus, joint proximal and remote sensing provides timely, easily accessible, and suitable data for extracting landscape factors. Highlights: Proximal and remote sensing data are suitable for extracting landscape factors. Hybrid statistical approaches were employed to map lead (Pb) in urban topsoil. Combined use of proximal and remote sensing improved the predictions of Pb contents. Geographically weighted regression outperformed regression kriging for mapping Pb. Abstract : Mapping heavy metal contamination in urban environment using proximal and remote sensing data, and hybrid statistical approaches used for modeling.